Are LLMs Useful in the Poorest Schools? theTeacherAI in Sierra Leone - Choi, Jun Ho; Garrod, Oliver; Atherton, Paul; Joyce-Gibbons, Andrew; Mason-Sesay, Miriam; Björkegren, Daniel (arXiv, 2023)
Education systems in developing countries have few resources to serve large, poor populations. How might generative AI integrate into classrooms? This paper introduces an AI chatbot designed to assist teachers in Sierra Leone with professional development to improve their instruction. We describe initial findings from early implementation across 122 schools and 193 teachers, and analyze its use with qualitative observations and by analyzing queries. Teachers use the system for lesson planning, classroom management, and subject matter. A subset of teachers use the system intensively. We draw conclusions from these findings about how generative AI systems can be integrated into school systems in low income countries.
Keywords: Computer Science - Computers and Society